Exploration and casting of large scale microscopic pathways for shale using electrodeposition. (1st August 2019) - Jin, Xu; Wang, Xiaoqi; Yan, Weipeng; Meng, Siwei; Liu, Xiaodan; Jiao, Hang; Su, Ling; Zhu, Rukai; Liu, He; Li, Jianming
Highlights: Electrodeposition was used to characterize microscopic pore throat system of shale. The pore throat systems that smaller than 10 nm can be observed. Both the surface area and interconnected pores ratio in the shale were revealed. The accuracy was confirmed by micro pore connectivity calculation method. Abstract: In unconventional petroleum reservoirs, such as shale gas, shale oil, tight oil, and tight gas reservoirs, the microscopic pore structure, namely, the size, geometry, distribution, and interconnected relations of the pores and throats of a shale rock, directly affects the porosity, storage, and permeability. Studies related to the microscopic pore structure of shale are considered important for evaluating shale resources and for elucidating their distribution characteristics; additionally, these studies aim to improve the productivity and recovery ratio of both oil and gas. Therefore, methods that can accurately characterize the microscopic pore structure of shale have received considerable attention. In this study, we used the electrodeposition method to fill the interconnected pores of a rock sheet with metal and then used selective dissolution of the rock portion of the rock sheet to obtain the metal complex of the pore-throat structure. The structure and morphology of the obtained metal complex, which represents the microscopic pore structure of the shale, are characterized by a scanning electron microscope (SEM). By combining electrochemical deposition and SEM images, we could directly observe the three-dimensional microstructure of the shale at a scale smaller than 50 nm with a large observation area. Additionally, the surface areas of the connected pores and throats of the shale were calculated.